PENGARUH PEER GROUP TERHADAP MOTIVASI BELAJAR REMAJA (Survei pada Siswa Kelas X SMA Negeri 21 Jakarta Timur Angkatan 22) - Kharisma Adisti Amalia (2020)
This study discusses about the impact of peer group towards adolescents learning motivation, especially for students. Learning motivation has a positive impact for students. One that often provides motivation to learn is the students of grade X SMA 21 East Jakarta. In this study, author used Social Learning Theory, with a quantitative approach by conducting a survey method using questionnaire. Correlation tests result between two variables, that is X variable as peer group towards Y variable as learning motivation, shows that there is a quite impactful correlation, that is as much as 0,536. While, the result of determination coefficient test are known to be 21,4%. Hypothesis test result, with t counted as 4,322 > t table as 1,667. So, it can be concluded that Ho is rejected and Ha is accepted, which means there are some impact between peer groups towards adolescents learning motivation which in this case is the students of grade X SMA Negeri 21 East Jakarta class of 22.